Analysis of D1853N ATM polymorphism in radiosensitive patients with cervical carcinoma - Beránek, Martin; Drastíková, Monika; Paulíková, Simona; Sirák, Igor; Vosmik, Milan; Petera, Jirí (Acta medica (Hradec Kralove), 2011)
UNLABELLED: Clinical oncologists have been focusing their efforts on attempting to define risk groups of patients with unusual biological reactions to the recommended therapy regimens using molecular biology techniques. THE AIMS OF OUR STUDY WERE: (i) to find a design and validate a method for fast and reliable analysis of the D1853N (5557G>A) genetic polymorphism in the ATM (ataxia-telangiectasia mutated) gene; (ii) to use side-directed mutagenesis to generate ATM 5557A-positive DNA (reference ATM5557A DNA); and (iii) to analyze a group of patients suffering from cervical carcinoma with adverse responses to radiotherapy. The 5557A variant was found in three of twenty women (15%). Our data show that the prevalence of the 5557A allelic variant in cervical cancer subjects with adverse responses after irradiation probably does not differ from the prevalence common in Caucasians. A larger population study should confirm these preliminary results.
Keywords: dospělí; proteiny buněčného cyklu; Polymorphism, Restriction Fragment Length; Humans; Polymerase Chain Reaction; lidé středního věku; Tumor Suppressor Proteins; Middle Aged; nádorové supresorové proteiny; sekvenční homologie nukleových kyselin; Sequence Analysis, DNA; Carcinoma, Squamous Cell; Polymorphism, Genetic; ATM protein; DNA-Binding Proteins; polymorfismus genetický; spinocelulární karcinom; Radiation Tolerance; Mutagenesis, Site-Directed; Adult; nádory děložního čípku; Sequence Homology, Nucleic Acid; polymorfismus délky restrikčních fragmentů; Uterine Cervical Neoplasms; DNA vazebné proteiny; polymerázová řetězová reakce; Ataxia Telangiectasia Mutated Proteins; Cell Cycle Proteins; mutageneze cílená; protein-serin-threoninkinasy; Protein Serine-Threonine Kinases; tolerance záření; ženské pohlaví; sekvenční analýza DNA; lidé; Female